Implementasi program Rehabilitasi Sosial Daerah Kumuh (RSDK) di Kelurahan Ploso, Kecamatan Tambaksari, Kota Surabaya - Awatar Wisya Fatwa (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2022)
This study discusses the implementation of Slum Area Social Rehabilitation (RSDK) policy in Ploso Village, Tambaksari District, Surabaya City. Implementation of policy is an action taken by stakeholders to achieve the objectives of the policies outlined. The implementation of Slum Area Social Rehabilitation policies aims to improve the lives of the people by means of home improvement and community empowerment to alleviate slums and poverty problems. This study uses the theory of policy implementation which implies that a policy implementation beside influenced by policy content is also influenced by the policy context. This study uses qualitative methods to understand the implementation of the Rehabilitasi Sosial Daerah Kumuh program. The results of this study include 1) Implementation of the Slum Area Social Rehabilitation program which includes the objectives, implementation process, roles and relations of the stakeholder actors in carrying out programs in the community. 2) Implications of the implementation of the Slum Area Social Rehabilitation program, and 3) Constraints in the implementation of the Slum Area Social Rehabilitation program in Ploso Village, Tambaksari District, Surabaya City.